Sunday

April 19, 2015

April 19, 2015

Posted by **Sarah** on Friday, June 15, 2012 at 12:13am.

a) y = -3x^2 + 5x - 4

b) f(x) = 6/x - 3/(x^2)

c) f(x) = (3x^2 - 4x)(x^3 + 1)

thank you in advance :)

- Calculus -
**Damon**, Friday, June 15, 2012 at 2:57amNow wait a minute, you try first.

- Calculus -
**Henry**, Monday, June 18, 2012 at 5:47pmis it

a) y'= -6x + 5

b) f'(x)= -6/x^2 + 6/x^3

c) f'(x)= 15x^4 + 6x - 16x^3 - 4

Calculus - Differentiate the following function: y= [x+1]/√x I tried y=[x+...

Calculus AP - 5.2 The Natural logarithmic function Differentiate the function ...

Math (Calculus II) - Rate of change proportional to size: P(t)= P(i)e^kt, where ...

Math (Calculus II) - Rate of change proportional to size: P(t)= P(i)e^kt, where ...

Calculus - Differentiate the function. y = e^(x+2)+8 y'=?

calculus - Differentiate the function. f(x)=3x ln 6x - 3x

trigo help! - 1. differentiate cos(3/x) 2. differentiate sin(4/x) 3. ...

calculus - Differentiate the function. S(R) = 4πR^2

calculus - Differentiate the function. g(x)= x^2(1-2x) g'(x)= i tried doing 2x(1...

calculus - Differentiate the function. h(x)= ln(x+ sqrt(x^2 -4))